Visual investigation of solid-liquid phase equilibria for nonflammable mixed refrigerant. Issue 1 (November 2015) - Lee, C; Yoo, J; Park, I; Park, J; Cha, J; Jeong, S
Abstract: Non-flammable mixed refrigerant (NF-MR) Joule Thomson (J-T) refrigerators have desirable characteristics and wide cooling temperature range compared to those of pure J-T refrigerators. However, the operating challenge due to freezing is a critical issue to construct this refrigerator. In this paper, the solid-liquid phase equilibria (i.e. freezing point) of the NF-MR which is composed of Argon, R14 (CF4 ), and R218 (C3 F8 ), has been experimentally investigated by a visualized apparatus. Argon, R14 and R218 mixtures are selected to be effectively capable of reaching 100 K in the MR J-T refrigerator system. Freezing points of the mixtures have been measured with the molar compositions from 0.1 to 0.8 for each component. Each test result is simultaneously acquired by a camcorder for visual inspection and temperature measurement during a warming process. Experimental results show that the certain mole fraction of Argon, R14, and R218 mixture can achieve remarkably low freezing temperature even below 77 K. This unusual freezing point depression characteristic of the MR can be a useful information for designing a cryogenic MR J-T refrigerator to reach further down to 77 K.